2008
DOI: 10.1158/1078-0432.ccr-08-0243
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Treatment with Bevacizumab Prolongs Survival in anIn vivoOvarian Cancer Model

Abstract: Purpose: Vascular endothelial growth factor (VEGF) plays a central role in tumor angiogenesis and is regarded as a promising therapeutic target.We hypothesized that treatment with bevacizumab, a humanized recombinant anti-VEGF monoclonal antibody, could enhance antitumor response to cisplatin and prolong survival in a murine ovarian cancer model. Experimental Design: We conducted an MTS assay to examine the effect of bevacizumab on proliferation of the VEGF producing human ovarian cancer cell lines in vitro. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 46 publications
4
56
0
1
Order By: Relevance
“…[3][4][5] Anti-VEGF therapies reduce tumor growth and ascites burden and enhance survival in murine models of EOC, [6][7][8] and treatment with the VEGF antagonist bevacizumab (Avastin) prolonged survival in mice when used as maintenance therapy after a complete response to cisplatin-based chemotherapy. 9 Several human phase II trials showed significant activity in EOC when bevacizumab was used as a single agent, suggesting that the blockade of VEGF signaling may prove effective in clinical disease. However, response rates were variable.…”
mentioning
confidence: 99%
“…[3][4][5] Anti-VEGF therapies reduce tumor growth and ascites burden and enhance survival in murine models of EOC, [6][7][8] and treatment with the VEGF antagonist bevacizumab (Avastin) prolonged survival in mice when used as maintenance therapy after a complete response to cisplatin-based chemotherapy. 9 Several human phase II trials showed significant activity in EOC when bevacizumab was used as a single agent, suggesting that the blockade of VEGF signaling may prove effective in clinical disease. However, response rates were variable.…”
mentioning
confidence: 99%
“…In a mouse model of ovarian cancer, treatment with bevacizumab in combination with paclitaxel significantly reduced tumor growth compared with paclitaxel alone (83.3% reduction in the combination arm versus 58.5% reduction in the paclitaxel alone arm) and resulted in the complete inhibition of ascites formation (Hu et al, 2002). Similarly, treatment with bevacizumab in combination with cisplatin significantly reduced tumor growth and ascites formation compared with cisplatin therapy alone (Mabuchi et al, 2008).…”
Section: Combination Therapymentioning
confidence: 99%
“…In patients with ovarian cancer, high serum VEGF levels was reported to be an independent risk factor for developing ascites formation (Cooper et al, 2002;Li et al, 2004;Hefler et al, 2006). In an in vivo investigation using an intraperitoneal ovarian cancer model, VEGF inhibition resulted in the complete inhibition of ascites formation (Mesiano et al, 1998;Mabuchi et al, 2008). Since patients with advanced or recurrent ovarian cancer frequently suffer from malignant ascites and require paracentesis for symptomatic relief, the ability of VEGF-targeting agents to inhibit ascites formation makes them attractive candidate treatments for ovarian cancer (Numnum et al, 2006).…”
Section: Vegf Expression and Ascites Formationmentioning
confidence: 99%
See 2 more Smart Citations